Generic Tacrolimus (Tacrobell®) Shows Comparable Outcomes to Brand-Name Tacrolimus in the Long-Term Period After Adult Deceased Donor Liver Transplantation - Kim JM; Joh JW; Choi GS; Lee SK (Dove Medical Press, 2019)
Jong Man Kim, Jae-Won Joh, Gyu-Seong Choi, Suk-Koo Lee Department of Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Republic of KoreaCorrespondence: Jae-Won JohDepartment of Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, Irwon-Ro 81, Gangnam-Gu, Seoul 06351, Republic of KoreaTel +82-2-3410-3466Fax +82-2-3410-0040Email jw.joh@samsung.comBackground: Generic tacrolimus (Tacrobell®) is commonly used in liver transplant patients in Korea. No previous studies have assessed the long-term efficacy and safety of generic tacrolimus for adult deceased donor liver transplantation (DDLT) patients. The aim of the present study was to evaluate the long-term efficacy and safety of generic tacrolimus compared to brand-name tacrolimus (Prograf®) in adult DDLT recipients.Methods: Two hundred sixty-five adult DDLTs were performed in our center between 2003 and 2017. To determine the efficacy and safety of generic tacrolimus, renal function (estimated glomerular filtration rate [eGFR] and creatinine), infectious complications, rejection-free survival rates, and patient survival rates were investigated.Results: Of 265 patients, 193 were selected and divided into a generic tacrolimus group (n=147) and a brand-name group (n=46). Mean follow-up duration was 63.2 ± 44.3 months. The 1-year, 3-year, 5-year, and 10-year patient survival rates were 89.1%, 86.9%, 84.5%, and 75.2%, respectively, in the generic tacrolimus group and 95.7%, 88.9%, 86.3%, and 83.7% in the brand-name tacrolimus group. There were no statistically significant differences in the infectious complications, new-onset diabetes, and renal dysfunction included mean serum creatinine level or eGFR after DDLT between the two groups. Increased recipient age, continuous renal replacement therapy (CRRT) in the pre-transplant phase, and acute rejection were predisposing factors for patient death.Conclusion: The present study shows that generic tacrolimus is an alternative comparable to brand-name tacrolimus in adult DDLT patients.Keywords: liver transplantation, immunosuppression, safety, efficacy